Crosstalk between the actin cytoskeleton and Ran-mediated nuclear transport. - Minakhina, S.; Myers, R.; Druzhinina, M.; Steward, R. (BMC Cell Biology, 2005)
Transport of macromolecules into and out of the nucleus is a highly regulated process. The RanGTP/RanGDP gradient controls the trafficking of molecules exceeding the diffusion limit of the nuclear pore across the nuclear envelope.We found genetic interaction between genes establishing the Ran gradient, nuclear transport factor 2 (ntf-2), Ran GTPase activating protein (Sd), and the gene encoding Drosophila Profilin, chickadee (chic). The severe eye phenotype caused by reduction of NTF2 is suppressed by loss of function mutations in chic and gain of function mutations in Sd (RanGAP). We show that in chic mutants, as in Sd-RanGAP, nuclear export is impaired.Our data suggest that Profilin and the organization of the actin cytoskeleton play an important role in nuclear trafficking.